2019
DOI: 10.3390/cryst9060284
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Carbonate Mineralization in a Surface-Tension-Confined Droplets Array

Abstract: Calcium carbonate biomimetic crystallization remains a topic of interest with respect to biomineralization areas in recent research. It is not easy to conduct high-throughput experiments with only a few macromolecule reagents using conventional experimental methods. However, the emergence of microdroplet array technology provides the possibility to solve these issues efficiently. In this article, surface-tension-confined droplet arrays were used to fabricate calcium carbonate. It was found that calcium carbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…2 b), comprised of an aggregation of many tiny crystals (Fig. 2 b) 16 . The SEM analysis showed that we obtained monodisperse particles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 b), comprised of an aggregation of many tiny crystals (Fig. 2 b) 16 . The SEM analysis showed that we obtained monodisperse particles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the laboratory scale, it is not easy to carry out high-throughput experiments with only a few macromolecule reagents using conventional experimental methods. In the fourth paper, He et al [4] explore the surface-tension-confined droplet arrays technique to fabricate CaCO 3 using polyacrylic acid as a modified organic molecule control. These authors prove the possibility of performing biomimetic crystallization and biomineralization experiments using this technique.…”
mentioning
confidence: 99%